Applicability of the Sustainability Model for Measuring the Success of Electronic Government Services - Faaeq, Munadil K.; Faieq, Alaa Khaleel; Rasheed, Mohammad M.; Dawod, Wajdi Hamza Alredany; Salami, Qusay H. Al- (International Journal of Engineering and Technology, 2018)
The Information and Communication Technologies (ICT) bring new challenges as well as a risky environment for sustainable development. In recent years the electronic government (eG) system has become an important component of Information Communication Technology provided by governments to sustain and facilitate all the transactions. Clearly, there is a lack of studies that identify the most important criteria of sustainability model of eG projects in specific and electronic project (e-project) in general. Additionally, the absence of an established model to measure the sustainability in developed and developing countries too. Therefore, this study attempted to design and validate sustainability model by examining the current situation of eG services in Iraq, a country characterized by an unstable environment. To examine the sustainability model, the data for this study were collected from the employees in public universities. Out of 700 questionnaires distributed, 436 questionnaires returned were useable. The findings of the study confirmed that the top important criterion that affects the sustainability of eG is the availability of services, especially the awareness of the availability of eG services. This is followed by cost, routine, speed, time, benefit, flexibility, and finally satisfaction. The ï¬ndings make another contribution to the academic literature on sustainability performance measures electronic project. In sum, this study demonstrated that the sustainability model is valid and can be utilized to examine sustainability towards various electronic projects in diverse cultures among different nations.